2022
DOI: 10.1002/fes3.361
|View full text |Cite
|
Sign up to set email alerts
|

Controlled‐release nitrogen fertilizer management influences grain yield in winter wheat by regulating flag leaf senescence post‐anthesis and grain filling

Abstract: Controlled‐release nitrogen fertilizer (CRNF) is expected to meet the nutrient demands for crop growth with single fertilizer application, so as to achieve high‐yield, high‐efficiency, and labor‐saving cultivation. However, under current CRNF practices, a single application of CRNF in winter wheat (Triticum aestivum L.) usually fails to achieve satisfactory effects due to insufficient nitrogen (N) supply in the later growth stage, contributing to premature leaf senescence and poor grain filling. To determine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This increased competition is further confirmed by the faster leaf senescence in the HL plants compared to the LL plants following the decrease in EC to 1000 µS cm −1 . Since flag-leaf photosynthesis plays an important role in grain filling [ 37 ], faster flag-leaf senescence eventually results in less assimilate availability during grain filling [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increased competition is further confirmed by the faster leaf senescence in the HL plants compared to the LL plants following the decrease in EC to 1000 µS cm −1 . Since flag-leaf photosynthesis plays an important role in grain filling [ 37 ], faster flag-leaf senescence eventually results in less assimilate availability during grain filling [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the economic benefits of different treatments, the wheat output and net benefit were calculated by the following formula ( Equations 4 , 5 ) ( Ma et al., 2022 ):…”
Section: Methodsmentioning
confidence: 99%
“…Due to the limited of nutrient release cycle, N release from one-time application of CRNF is difficult to cover the entire wheat growth period. As a result, although one-time application of CRNF can satisfy N supply for tiller differentiation at the seedling stage, it easily leads to N deficiency in the later stage of wheat, which limits the matter accumulation and grain filling post-anthesis (Ma et al, 2022). The study on wheat grown in paddy soil by Ji et al ( 2012) also confirmed that one-time application of CRNF reduced the volatilization of NH 3 and the emissions of N 2 O in wheat fields compared to common urea, but did not significantly improve the wheat yield and NUE.…”
Section: Introductionmentioning
confidence: 99%
“…Flag leaves contribute the majority of assimilates for grains during post-anthesis stages and increased N supply results in increased leaf area, leaf nitrogen and chlorophyll content in wheat flag leaves (Tamang et al 2017). Flag leaf senescence and photosynthesis performance are highly regulated by N supply which plays a vital role in the grain-filling process and alters dry matter accumulation (Ma et al 2022). Although flag leaf δ 15 N results showed that flag leaf nitrogen increased to comparably extents under drought conditions.…”
Section: Flag Leaf δ 15 N Valuementioning
confidence: 99%